Cyanosilylation of Aldehydes Catalyzed by MIL‐101(Cr): A Theoretical Investigation. Issue 26 (12th September 2017) - de Oliveira, Aline; Mavrandonakis, Andreas; de Lima, Guilherme F.; De Abreu, Heitor A.
Abstract: The Metal‐Organic Frameworks (MOFs) compose a class of solids with promising applicability. There are many different structures and many distinct ways to synthesize new solids based on previously known MOFs. The understanding of these materials at molecular level is very important, because it can assist the design of solids with optimized properties to a desired application. The cyanosilylation of aldehydes is a reaction which can be used to evaluate the catalytic performance of a material as Lewis acid or base. However, it is experimentally difficult to identify the most relevant sites. In this work, DFT calculations were used aiming to get information about the important chemical structural characteristics of the MOF MIL‐101(Cr) which explain its catalytic activity to the cyanosilylation reaction. The investigation shows that when this MOF acts as a Lewis acidic catalyst the cyanosilylation is 10 10 times faster than the non‐catalyzed process. Abstract : The Metal‐Organic Frameworks (MOFs) compose a class of solids very promising to be applied as catalysts. There are many ways to design these materials and new ones can be prepared with optimized properties. In this work, the most likely catalytic sites of the MOF MIL‐101(Cr) are investigated through a mechanistic study of the cyanosilylation reaction. The information obtained at molecular level to this process can assist the design of new materials.